2010
DOI: 10.1107/s1744309109055109
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure of the NO-bound CuBin bovine cytochromecoxidase

Abstract: The X-ray crystallographic structure of nitric oxide-treated bovine heart cytochrome c oxidase (CcO) in the fully reduced state has been determined at 50 K under light illumination. In this structure, nitric oxide (NO) is bound to the CcO oxygen-reduction site, which consists of haem and a Cu atom (the haem a(3)-Cu(B) site). Electron density for the NO molecule was observed close to Cu(B). The refined structure indicates that NO is bound to Cu(B) in a side-on manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…A recent crystal structure of the bovine aa 3 -CO shows that CO binds to CuB+ in a side-on fashion after photolysis of CO from heme italica32+. The CuB+-to-carbon and CuB+-to-oxygen atom distances of 2.4 and 2.7 Å, respectively, indicate a very weak CuB+ – CO bond [44,45]. Significantly, no infrared linear dichroism was observed for the transient photoproduct of the CO-bound bovine aa 3 , which was interpreted in terms of CO being bound to CuB+ at the “magic angle” to the heme normal [46]; another explanation is that the photodissociated CO does not bind to CuB+.…”
Section: Ligand Binding In the Heme-copper Oxidasesmentioning
confidence: 99%
“…A recent crystal structure of the bovine aa 3 -CO shows that CO binds to CuB+ in a side-on fashion after photolysis of CO from heme italica32+. The CuB+-to-carbon and CuB+-to-oxygen atom distances of 2.4 and 2.7 Å, respectively, indicate a very weak CuB+ – CO bond [44,45]. Significantly, no infrared linear dichroism was observed for the transient photoproduct of the CO-bound bovine aa 3 , which was interpreted in terms of CO being bound to CuB+ at the “magic angle” to the heme normal [46]; another explanation is that the photodissociated CO does not bind to CuB+.…”
Section: Ligand Binding In the Heme-copper Oxidasesmentioning
confidence: 99%
“…The biological Cu A site is a binuclear copper center in cytochrome c oxidase (C c O)1–14 and nitrous oxide reductase (N 2 OR) 15–18. It can perform rapid long‐range electron transfer from an electron source such as cytochrome c 2–5.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and theoretical studies have revealed geometrical and electronic properties of the Cu A site 1–37. Three‐dimensional X‐ray crystallographic structures of the Cu A site from C c O, N 2 OR, and engineered blue copper proteins show the characteristic structural feature, as shown in Figure 1 6–14, 17–19. It is composed of two copper ions bridged by the thiolate groups of two conserved Cys residues, and each copper ion is coordinated equatorially with a His residue and axially with either a Met residue or a peptide carbonyl group.…”
Section: Introductionmentioning
confidence: 99%
“…If the spectral features of resting CcO are correctly interpreted, a more likely coordination mode for the peroxo to Cu is η 2 , [31] as in the recent crystallographic structure of a side-on nitrosyl bound to Cu B in CcO. [32] …”
mentioning
confidence: 99%